(untitled) (Web of Technology: Multidimensional Research Journal, 2025)
The work used seeds of flax of the oilseed variety "Bakhmalskiy-2" (lat. Línum usitatíssimum L.), obtained at Zamona Rano LLC (Tashkent region, Uzbekistan). Oil flax is a highly profitable crop, one of the advantages of which is drought resistance, which is a very weighty argument for republics with an arid climate, in particular for Uzbekistan. In addition, oil flax has a simple cultivation technology that does not require the use of insecticides, which increases its food safety.